Sisterhood, Interrupted - Siegel, D. author. aut Link
XIV, 224 p.
Keywords: Contrary to clichés about the end of feminism, Deborah Siegel argues that younger women are not abandoning the movement but reinventing it. After forty years, is feminism today a culture, or a cause? A movement for personal empowerment, or broad-scale social change? Have women achieved equality, or do we still have a long way to go?